Perception Towards E-payment among Youths in Pokhara - Budhathoki, Dhruba Kumar (Journal of Nepalese Business Studies, 2020)
This paper analyzes the perception of youth towards E-payment in Pokhara along with the consideration of gender, age, product attributes, psychological traits on the perception of youths towards e-payment gateway. This study has adopted a descriptive and causal research design. A total of 160 respondents were selected for study purposes using the convenience sampling method from Pokhara valley. The modified Likert scale questionnaire was used to gather data about the perception of youths towards e-payment. The results indicate that 70% of respondents prefer E-Sewa, moreover, gender, age, occupation do not affect the perception of youths towards e-payment but academic qualification affects the perception of youths towards e-payment. Similarly, trustworthiness and product safety do not affect the perception of youths.